2013
DOI: 10.1007/s10787-013-0172-x
|View full text |Cite
|
Sign up to set email alerts
|

The modern pharmacology of paracetamol: therapeutic actions, mechanism of action, metabolism, toxicity and recent pharmacological findings

Abstract: Paracetamol is used worldwide for its analgesic and antipyretic actions. It has a spectrum of action similar to that of NSAIDs and resembles particularly the COX-2 selective inhibitors. Paracetamol is, on average, a weaker analgesic than NSAIDs or COX-2 selective inhibitors but is often preferred because of its better tolerance. Despite the similarities to NSAIDs, the mode of action of paracetamol has been uncertain, but it is now generally accepted that it inhibits COX-1 and COX-2 through metabolism by the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
405
1
21

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 515 publications
(465 citation statements)
references
References 274 publications
11
405
1
21
Order By: Relevance
“…Unknown quantities of partially metabolised drugs which may be toxic are also released in faeces and urine. 21 Their molecular sizes in the nanometre (10 -9 ) and Angstrom range (10 -10 ) make it impossible for marine organisms to exclude them. It has been widely reported that these compounds are continuously released into the environment, [22][23][24] and bioaccumulate in wild-caught fish populations at concentrations of nanograms per gram.…”
Section: Discussionmentioning
confidence: 99%
“…Unknown quantities of partially metabolised drugs which may be toxic are also released in faeces and urine. 21 Their molecular sizes in the nanometre (10 -9 ) and Angstrom range (10 -10 ) make it impossible for marine organisms to exclude them. It has been widely reported that these compounds are continuously released into the environment, [22][23][24] and bioaccumulate in wild-caught fish populations at concentrations of nanograms per gram.…”
Section: Discussionmentioning
confidence: 99%
“…Interest in the Jaborandi plant by French physicians was piqued due to its use among Brazilian Indians to promote profuse sweating and salivation. 2 Because of its commercial value, this species was exploited without control and by the 1990s it was considered an endangered species in Brazil. 1 During the dry season collectors go into the forest and strip the leaves from branches by hand.…”
Section: Endangered Jaborandimentioning
confidence: 99%
“…Excessive and frequent collection of leaves from the same plant does not allow full development of new leaves leading to high plant mortality and reduction in the size of new leaves. 2 Studies are being carried out to establish the biosynthetic route…”
Section: Endangered Jaborandimentioning
confidence: 99%
See 1 more Smart Citation
“…If closure of the PAD is not achieved with one or two cycles of NSAID therapy, surgical closure is indicated 16 . More recently, paracetamol has been used, however clinical experience is still under development 17,18 .…”
Section: Introductionmentioning
confidence: 99%